Geometrical Error Modeling of Large Modulus Modified Wind Power Gear based on Form Grinding - Jiong Wang; Shihang Yu; Yuwen Sun (Jixie chuandong)
Due to properties of reducing impact，improving uneven load，and lowering noise in the meshing process，the technology of tooth surface modified are very common in the wind power gear. As the last process of machining gear，form grinding determines the accuracy of gear directly. Therefore，solving geometry error of form grinding becomes vital for optimize grinding tool path and enhancing the machining precision. Thus，this paper builds a model of geometrical error. In order to solve the geometry error of form grinding， firstly， tooth surface model of gears combining the profile and axial modification （including drum and helix modification） is constructed. Then，based on the tooth surface parameter，the length of common perpendicular between axes of the gear and the wheel，the contacting curve between the gear and the wheel is solved. The form grinding tooth surface is constructed. Finally，the geometrical error of tooth surfuce form grinding is defined by using the theoretical tooth surface and form grinding tooth surface， the geometric error model of tooth surface form grinding is established， some suggestions are given to reduce the geometry error of form grinding.